Integrating mental health care into primary care: the case of one rural district in Rwanda. Issue 2 (July 2017) - Smith, Stephanie L.; Kayiteshonga, Yvonne; Misago, Claire N.; Iyamuremye, Jean Damascene; Dusabeyezu, Jeanne d'Arc; Mohand, Achour A.; Osrow, Robyn A.; Anatole, Manzi; Daimyo, Shin; Uwimana, Eugenie; Dushimiyimana, Dominique; Raviola, Giuseppe J.
Abstract : N/A: Integration of mental health care into primary care is a strategic priority of Rwanda's national mental health care programme and a central tenet of global mental health. In 2009, the international health care delivery organisation, Partners In Health, established a community based mental health programme to support national planning goals. In 2012, the organisation collaborated with the Rwanda Ministry of Health to implement a structured mentorship programme enabling government employed, primary care nurses to care for patients with severe mental disorders at primary care health care centres in one rural district. The implementation strategy included decentralised training and consistent supervision for four priority neuropsychiatric disorders. Lessons learned were applied through the transition of supervisory responsibilities to district hospital based government nurses. The programme's focus on structured mentorship for generalist nurses, systems based improvements and use of an existing public health care strengthening efforts highlight its potential as a model for integrating mental health care into primary care in resource limited settings.